2020
DOI: 10.1016/j.clnesp.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and vitamin D in paediatric intestinal failure patients receiving home parenteral nutrition

Abstract: Background & aims: Patients with intestinal failure (IF) are dependent on long-term home parenteral nutrition (HPN) to ensure growth and development. The primary aim of the present study was to assess bone mineral density (BMD) and vitamin D status in paediatric IF patients on HPN and a group of healthy children aged 2e18 years. Secondary aims were to assess growth, body composition, nutrient provision and physical activity. Methods: An observational cross-sectional study was performed at Oslo University Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 42 publications
(42 reference statements)
2
22
0
Order By: Relevance
“…One further article was included by reference snowballing. Twenty studies were included in the final review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One further article was included by reference snowballing. Twenty studies were included in the final review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies were observational, and six included a control group (case-control studies) [ 18 , 19 , 20 , 24 , 25 , 34 ]. All except one were single-center studies: 7 from U.S. centers [ 16 , 18 , 19 , 22 , 26 , 27 , 28 ], 1 from Canada [ 25 ], and 11 from Europe [ 17 , 20 , 21 , 23 , 24 , 29 , 30 , 31 , 32 , 33 , 34 ], and 1 study reported data from 2 U.S. centers [ 24 ]. The 20 studies included patients from 15 different cohorts (6 studies from 3 cohorts [ 17 , 21 , 29 , 30 , 33 , 34 ]) and 3 studies from one cohort [ 19 , 22 , 24 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations